MA-activated lattice shrinkage and bandgap renormalization advancing the stability of FA1-xMAxPbI3 (x=0–1) perovskites photovoltaic - Congtan Zhu; Xueyi Guo; Si Xiao; Weihuang Lin; Zhaozhe Chen; Lin Zhang; Hui Zhang; Xiangming Xiong; Ying Yang (Advanced Powder Materials)
Generally, referring to the stability of perovskite, the most studied perovskite material has been MA-free mixed-cation perovskite. The precise role of MA in the light-thermal-humid stability of perovskite solar cells still lacks of a systematically understanding. In this work, the evolution of crystallographic structures, intermediate phase, ultrafast dynamics, and thermal decomposition behavior of MA-mixed perovskite FA1-xMAxPbI3 (x=0–100%) are investigated. The influence of MA on the stability of devices under heat, light, and humidity exposure are revealed. In the investigated compositional space (x=0–100%), device efficiencies vary from 19.5% to 22.8%, and the light, thermal, and humidity exposure stability of the related devices are obviously improved for FA1-xMAxPbI3 (x=20%–30%). Incorporation 20%–30% of MA cations lowers nucleation barrier and causes a significant volume shrinkage, which enhances the interaction between FA and I, thus improving crystallization and stability of the FA1-xMAxPbI3. Thermal behavior analysis reveals that the decomposition temperature of FA0.8MA0.2PbI3 reaches 247 ​°C (FAPbI3, 233 ​°C) and trace amounts of MA cations enhance the thermal stability of the perovskite. Remarkably, we observe lattice shrinkage using spherical aberration corrected transmission electron microscope (AC-TEM). This work implies that stabilizing perovskites will be realized by incorporating trace amounts of MA, which improve the crystallization and carrier transport, leading to improved stability and performances.